Molecular genetics of maple syrup urine disease in the Turkish population - Gorzelany, Kerstin; Dursun, Ali; Coşkun, Turgay; Kalkanoğlu-Sivri, Serap H; Gökçay, Gülden Fatma; Demirkol, Mübeccel; Feyen, Oliver; Wendel, Udo (The Turkish Journal of Pediatrics, 2009)
In maple syrup urine disease (MSUD), disease-causing mutations can affect the BCKDHA, BCKDHB or DBT genes encoding for the E1alpha, E1beta and E2 subunits of the multienzyme branched-chain alpha-keto acid dehydrogenase (BCKDH) complex. Here we summarize the MSUD genotypes of a cohort of 32 unrelated Turkish patients in whom both alleles at a single gene locus harbored presumable disease-causing nucleotide changes. The patients had different forms of MSUD, ranging from the severe classical form (26 patients) to severe and mild variants (6 patients). In all except two patients (92%), the mutations occurred homozygously. The mutational spectrum included 27 different sequence variations–12 changes in the BCKDHA, 10 in the BCKDHB, and 5 in the DBT genes. In 37% (12 patients) of a total of 64 alleles, the supposed disease-causing mutations were located in the BCKDHA gene, in 44% (14 patients) in the BCKDHB gene and in 19% (6 patients) in the DBT gene. The mutational profile is heterogeneous, although two mutations occurred three times and five mutations occurred twice. There was no cluster for a single mutation except for c.773G>A (p.Cys258Tyr) in the BCKDHA gene, a hypothetical founder mutation in the Camlidere population.